Albert Watkins and Howard Watkins Family Genealogy Trip to Tennessee - Watkins, Howard::::::::: (1986)
Helen Greenfield, Albert Watkins, Exie Neander, Howard Neander and Estelle Kelsey at Chattanooga Choo-Choo